Development of E-Atlas of Solanaceae Morphology and Anatomy for Higher Education - Aini, Nur; Karim, Hilda; Syamsiah, Syamsiah (Universitas Negeri Makassar, 2025)
Abstract. The development of an e-atlas of the morphology and anatomy of Solanaceae plants serves as a digital-based supporting learning resource that can be utilized in higher education. The product contains direct observation results of plant morphology and anatomy conducted in the Biology Laboratory of FMIPA UNM. The purpose of this research and development (R&D) was to produce an e-atlas as a valid and practical biology learning resource for the Plant Structure and Development course. This study employed the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. The results showed that the e-atlas was declared valid by expert validators with a validity score of 1 (valid category). The practicality test based on lecturers’ responses reached 90.62%, and student responses reached 85.66%, indicating that the e-atlas is highly practical with positive feedback. Thus, it can be concluded that the developed e-atlas of morphology and anatomy of Solanaceae plants is valid and practical.Keywords: e-atlas, learning resource, practical, valid